O Zastosowaniu Metody Kruchych Pokryć do Wyznaczania Charakteru i Obszarów Odkształceń Plastycznych Metali - Pindera, J.T. (Engineering Transactions, 1957)
The author presents the results of his investigations concerning the application of the method of brittle coatings for the determination of plastic deformation of metals on the basis of the phenomenon of loss of adhesion as between the layer of brittle coating and the metal, when the body undergoes a plastic deformation. Since the method described requires no special preparation of the surface of the body except the removal of the corroded layer and polishing, it is easier and less expensive than.other methods. The boundaries of the regions of plastic deformation are clearly visible. The author compares the results obtained with theoretical solutions.